2008
DOI: 10.1080/09537100701230444
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rosuvastatin treatment on the mean platelet volume in patients with uncontrolled primary dyslipidemia with hypolipidemic diet treatment

Abstract: Platelet activation and aggregation are central processes in the pathophysiology of coronary heart disease. Mean platelet volume (MPV), a determinant of platelet activation, is a newly emerging risk marker for atherothrombosis. Rosuvastatin, a new hydrophilic 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor (statin), is approved as an adjunct to diet in patients with dyslipidemia. In this study, we evaluated the effects of rosuvastatin on the MPV levels in patients with uncontrolled primary dyslipidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 30 publications
3
65
2
3
Order By: Relevance
“…Bellucci et al also observed an increase in platelet volume in patients treated with anagrelide [32]. Coban et al found that treatment with rosuvastatin decreased in a significant way the MPV values [33]. In our study we found similar results in a subgroup of 13 patients who underwent treatment with simvastatin.…”
Section: Discussionsupporting
confidence: 81%
“…Bellucci et al also observed an increase in platelet volume in patients treated with anagrelide [32]. Coban et al found that treatment with rosuvastatin decreased in a significant way the MPV values [33]. In our study we found similar results in a subgroup of 13 patients who underwent treatment with simvastatin.…”
Section: Discussionsupporting
confidence: 81%
“…Taken together, the more recent findings 28 and those from the earlier studies suggest that rosuvastatin 23,24 and atorvastatin, 25,26 but not pravastatin, 27 exert an additional beneficial action on MPV. With rosuvastatin this action is not mediated by the improved serum lipids, 28 whereas atorvastatin achieved a significant MPV reduction in patients with the strongest concomitant lipid changes.…”
mentioning
confidence: 66%
“…23,24 Of note, there was no correlation between reduction in MPV and improvement in serum lipids following treatment. 23,24 Atorvastatin can also decrease the MPV. 25,26 Of note, this beneficial effect appears to be more pronounced in patients exhibiting the strongest lipid reduction.…”
mentioning
confidence: 99%
See 2 more Smart Citations